Will Eisner’s The Spirit re-signified by Frank Miller in the iniquitous spaces of fictional dark cities (Intercom - Brazilian Journal of Communication Sciences, 2022)
The article takes as objects of study Will Eisner’s graphic narratives, originating in the 1940s, and their adaptation, which Frank Miller scripted and directed, in the film The Spirit (2008). Methodologically, we developed a comparative aesthetic analysis, with a contribution to the intersemiotic processes observed in the passage from print media to cinema. We started from the observation of spatial coordinates in fictional dark cities, which present themselves as iniquitous and violent symbolic scenarios, conducive to the actions of villains and problematic detectives. Next, we point out the reverberations coming from the German expressionist cinema and from cinema noir in the represented urban spaces; highlighting the atmosphere of sexualization linked to the femmes fatales. To conclude, we detailed techno-aesthetic aspects of the translation option of Eisner’s work, inserting it into Miller’s graphic-cinematic project; with an emphasis on stylization as evocation and as metamorphosis.
Keywords: Sequential Art; Film adaptation; Will Eisner; Frank Miller